Optimalisasi Peran Filantropi Islam Aksi Cepat Tanggap dalam Upaya Mengatasi Krisis Ekonomi di Era Pandemi Covid-19 - Janah, Wadzifatul (Institut Agama Islam Negeri Ponorogo, 2021)
This study aims to determine the efforts and strategies of the Islamic philanthropic institution Aksi Cepat Tanggap (ACT) in overcoming the economic crisis in the current Covid-19 pandemic era. By optimizing the existing potential of ZISWAF to overcome problems of the ummah and humanity. Producing zakat and waqf assets, socializing the real ZISWAF, and collaborating with all existing philanthropic-based non-profit organizations. The research method used is qualitative descriptive, this research is a qualitative research with a type of case study (case study).